Decision in Shopping In the Charity of an Islamic Community Organization - Mansur Azis; Said Abadi; Faisa Nurdiantini (Niqosiya: Journal of Economics and Business Research, 2024)
A purchasing decision is a process of making choices by integrating knowledge used to combine knowledge and evaluating two or more alternatives. Strategy is the primary key to survival and growth; besides that, consumers are also the most critical assets for a company's survival. If a company can meet or satisfy the desires of consumers, it will get loyalty from its consumers; the company is legally obliged to study marketing strategies to influence consumers to decide to buy; the purpose of this research is to identify and analyze the influence and marketing (product, price, place, promotion, people, process, and physical evidence) applied by Surya Mart and Nusantara Mart Rationally and simultaneously on consumer decisions, l. The method used in this study is Quantitative, linear regression. The results of this study are 1) from the results of the quantitative test, the product sig value is 0.00, price 0.00, promotion 0.00, people 0.01, process 0.00, physical evidence 0.00, all of which are <0.05, which means that six marketing strategies have a significant effect on consumer decisions and only one is less effective in influencing place<0.05. Meanwhile, the simultaneous test results were 0.00<0.05, which means that marketing strategies (marketing (products, prices, places, promotions, people, processes, and physical evidence) simultaneously positively affect consumer decisions.